Roadbed Sedimentation on Folded Bases with Weak Soils - Shapoval, V. H; Ivanova, H. P; Tereshchuk, R. M; Nesterova, O. V. (Science and Transport Progress, 2021)
Purpose. The main purpose of the work is to construct accurate analytical dependences of the sedimentation of the roadbed base on its coordinates and the trapezoidal external load applied to the upper limit of the base. This will allow the foundation settlement profile to be calculated within and outside the embankment using the layer-by-layer stacking method. Methodology. Theoretical studies of geomechanical processes using analytical and numerical mathematical methods were applied to achieve the purpose, as well as analysis and generalization of the results of theoretical research. Findings. Analytical dependences of vertical and horizontal normal deformations on the half-plane coordinates to the upper limit of which the trapezoidal load is applied were obtained within the framework of the base model in the form of a linear elastic isotropic medium and the calculated scheme of planar deformation. On this basis, an algorithm for constructing a profile of a roadbed sedimentation made of soil materials has been developed. Originality. Analytical dependences of vertical normal deformations in the roadbed base with a trapezoidal profile on its coordinates are obtained. Practical value. The research materials presented in this work make it possible to construct the design profile of the roadbed of soil materials, taking into account the strong compressibility of the soil. In addition, the results obtained can be used to determine the lower limit of the compressible strata of the bases, to the upper limit of which a distributed load of either a triangular or a trapezoidal form is applied.